Inovasi Pemasaran Produk Emping Dan Kripik Tempe Di Umkm Desa Brokoh : Pendekatan Kuliah Kerja Nyata - Hanna Syahria; Dwiki Aditya; Devina Febriyanti; Nur Habibatus; Neno Sri; Arjuna Luqman; Anita Dyah; Daud Rismana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to increase sales and national market expansion for Micro, Small, and Medium Enterprises (MSMEs) in Brokoh Village, Batang Regency, through marketing innovations for tempeh chips. MSMEs in the food sector, especially those based on local products such as tempeh chips, have great potential to grow, but are often hampered by limited market access and digital marketing knowledge. This research utilizes the Community Service Program (KKN) approach to provide direct assistance to local MSMEs. Through field surveys, marketing strategy development, product innovation, and promotion, the research successfully introduced new flavors, more attractive packaging designs, and effective promotional strategies. The results of this study showed that the innovative approach was able to strengthen product identity, improve competitiveness, and expand the market reach of MSMEs at the national level. The impact is expected to encourage sustainable growth for MSMEs in Brokoh Village and improve the welfare of the local community.